2014
DOI: 10.1016/j.nicl.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain structure in youth who commit homicide

Abstract: BackgroundViolence that leads to homicide results in an extreme financial and emotional burden on society. Juveniles who commit homicide are often tried in adult court and typically spend the majority of their lives in prison. Despite the enormous costs associated with homicidal behavior, there have been no serious neuroscientific studies examining youth who commit homicide.MethodsHere we use neuroimaging and voxel-based morphometry to examine brain gray matter in incarcerated male adolescents who committed ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 47 publications
5
33
0
4
Order By: Relevance
“…And indeed, youth with these traits appear to be at risk to commit some of the most severe acts of violence. Cope and colleagues [60] found that incarcerated adolescents who had committed murder scored significantly higher in psychopathic traits than incarcerated adolescents who had not murdered. In this sample, the CU features of psychopathy appeared to most strongly distinguish youth who had committed homicide, evincing a moderately large effect size ( d = 0.87) [60].…”
Section: Psychopathy and Violencementioning
confidence: 99%
See 3 more Smart Citations
“…And indeed, youth with these traits appear to be at risk to commit some of the most severe acts of violence. Cope and colleagues [60] found that incarcerated adolescents who had committed murder scored significantly higher in psychopathic traits than incarcerated adolescents who had not murdered. In this sample, the CU features of psychopathy appeared to most strongly distinguish youth who had committed homicide, evincing a moderately large effect size ( d = 0.87) [60].…”
Section: Psychopathy and Violencementioning
confidence: 99%
“…Cope and colleagues [60] found that incarcerated adolescents who had committed murder scored significantly higher in psychopathic traits than incarcerated adolescents who had not murdered. In this sample, the CU features of psychopathy appeared to most strongly distinguish youth who had committed homicide, evincing a moderately large effect size ( d = 0.87) [60]. 4 Agar [57] found that among youth homicide offenders, psychopathy was associated with a higher degree of instrumentality, sexual violence, and gratuitous violence (i.e., “excessive violence beyond the level necessary to accomplish the homicide and/or caused the victim unnecessary pain and suffering”).…”
Section: Psychopathy and Violencementioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of literature supports this paralimbic hypothesis suggesting individuals with elevated psychopathic traits exhibit aberrant structure (specifically reduced grey matter volume and density) and function in many regions: anterior cingulate cortex (ACC), bilateral amygdala, bilateral hippocampus, medial orbitofrontal cortex (mOFC), bilateral orbitofrontal cortex (OFC), bilateral parahippocampus, posterior cingulate cortex (PCC), & bilateral temporal pole (Figure 1). Adults and youth with elevated psychopathic traits exhibit similar paralimbic neural dysfunction (Blair, 2006; Budhani and Blair, 2005; Cope et al, 2014; Ermer et al, 2012; Ermer et al, 2013; Harenski et al, 2014; Kiehl, 2006; Lockwood et al, 2013; Marsh et al, 2008; Motzkin et al, 2011; Raine et al, 2003). Deficits appear to be specific to the orbitofrontal cortex (Budhani and Blair, 2005; Cope et al, 2014; Ermer et al, 2013), insula (Lockwood et al, 2013), amygdala (Harenski et al, 2014; Marsh et al, 2008), PCC (Ermer et al, 2013), parahippocampal gyrus (Ermer et al, 2013), and ACC (Cope et al, 2014; Ermer et al, 2013; Marsh et al, 2008).…”
Section: 0 Introductionmentioning
confidence: 99%